PENGARUH KOMBINASI MASSASE DAN COUNTER PRESSURE TERHADAP NYERI PERSALINAN KALA I DI WILAYAH KABUPATEN CILACAP - Lina Puspitasari; Fatimah Azzahroh (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Cilacap, 2022)
Labor pain is a problem that cannot be overcome until now. Almost all pregnant women experience labor pain. This can result in stress, smooth muscles tighten and blood vessels narrow, uterine contractions decrease and oxygen supply decreases, and uterine ischemia occurs. Counter pressure massage techniques are often used to overcome these problems. However, this technique has not been combined with lumbar massage. So there is a need for further research on this technique. The research design is qualitative with a case study research strategy. The research subjects taken were 3 informants at BPM